SOME STRUCTURAL AND GEOMORPHOLOGICAL ASPECTS OF RECENT CRUSTAL MOVEMENTS IN ESTONIA - Raukas A.; Tavast E.; Vaher R. (My University, 1988)
Comparison of some structure contour of northeastern and southeastern Estonia with the bedrock relief patterns leads to the conclusion that direct morphostructures are infrequent in those areas. The formation of bedrock and contemporary relief has been little effected by differential postglacial and recent crustal movements. Morphotectonic analysis enables us to determine the character of those movements only in a few cases.